Activating enhancer binding protein 2 epsilon (AP-2?)-deficient mice exhibit increased matrix metalloproteinase 13 expression and progressive osteoarthritis development - Niebler, Stephan; Schubert, Thomas; Hunziker, Ernst B.; Boßerhoff, Anja Katrin (Arthritis Research & Therapy, 2015)
The transcription factor activating enhancer binding protein 2 epsilon (AP-2?) was recently shown to be expressed during chondrogenesis as well as in articular chondrocytes of humans and mice. Furthermore, expression of AP-2? was found to be upregulated in affected cartilage of patients with osteoarthritis (OA). Despite these findings, adult mice deficient for AP-2? (Tfap2e(-/-)) do not exhibit an obviously abnormal cartilaginous phenotype. We therefore analyzed embryogenesis of Tfap2e(-/-) mice to elucidate potential transient abnormalities that provide information on the influence of AP-2? on skeletal development. In a second part, we aimed to define potential influences of AP-2? on articular cartilage function and gene expression, as well as on OA progression, in adult mice.Murine embryonic development was accessed via in situ hybridization, measurement of skeletal parameters and micromass differentiation of mesenchymal cells. To reveal discrepancies in articular cartilage of adult wild-type (WT) and Tfap2e(-/-) mice, light and electron microscopy, in vitro culture of cartilage explants, and quantification of gene expression via real-time PCR were performed. OA was induced via surgical destabilization of the medial meniscus in both genotypes, and disease progression was monitored on histological and molecular levels.Only minor differences between WT and embryos deficient for AP-2? were observed, suggesting that redundancy mechanisms effectively compensate for the loss of AP-2? during skeletal development. Surprisingly, though, we found matrix metalloproteinase 13 (Mmp13), a major mediator of cartilage destruction, to be significantly upregulated in articular cartilage of adult Tfap2e(-/-) mice. This finding was further confirmed by increased Mmp13 activity and extracellular matrix degradation in Tfap2e(-/-) cartilage explants. OA progression was significantly enhanced in the Tfap2e(-/-) mice, which provided evidence for in vivo relevance. This finding is most likely attributable to the increased basal Mmp13 expression level in Tfap2e(-/-) articular chondrocytes that results in a significantly higher total Mmp13 expression rate during OA as compared with the WT.We reveal a novel role of AP-2? in the regulation of gene expression in articular chondrocytes, as well as in OA development, through modulation of Mmp13 expression and activity.
EVALuna2:4711

Hypoxia-Inducible Factor 1 Is an Inductor of Transcription Factor Activating Protein 2 Epsilon Expression during Chondrogenic Differentiation - Niebler, Stephan; Angele, Peter; Kujat, Richard; Boßerhoff, Anja Katrin (BioMed Research International, 2015)
The transcription factor AP-2? (activating enhancer-binding protein epsilon) is expressed in cartilage of humans and mice. However, knowledge about regulatory mechanisms influencing AP-2? expression is limited. Using quantitative real time PCR, we detected a significant increase in AP-2? mRNA expression comparing initial and late stages of chondrogenic differentiation processes in vitro and in vivo. Interestingly, in these samples the expression pattern of the prominent hypoxia marker gene angiopoietin-like 4 (Angptl4) strongly correlated with that of AP-2? suggesting that hypoxia might represent an external regulator of AP-2? expression in mammals. In order to show this, experiments directly targeting the activity of hypoxia-inducible factor-1 (HIF1), the complex mediating responses to oxygen deprivation, were performed. While the HIF1-activating compounds 2,2'-dipyridyl and desferrioxamine resulted in significantly enhanced mRNA concentration of AP-2?, siRNA against HIF1? led to a significantly reduced expression rate of AP-2?. Additionally, we detected a significant upregulation of the AP-2? mRNA level after oxygen deprivation. In sum, these different experimental approaches revealed a novel role for the HIF1 complex in the regulation of the AP-2? gene in cartilaginous cells and underlined the important role of hypoxia as an important external regulatory stimulus during chondrogenic differentiation modulating the expression of downstream transcription factors.
EVALuna2:4720